THE ANALYSIS OF SPIRIT OF WORK WITHIN MANADO STATE PROSECUTOR'S OFFICE - Meygi Nia Naomi Boky; David P. E. Saerang; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2022)
Abstract: The main issues nowadays regarding spirit of work is the way for sustaining the spirit of work; the issue arise because every individual or employees have different problems altogether which makes it difficult for the company to handle. In this particular research, Manado’s State Prosecutors Office which filled with different individuals with different needs that need to be uphold as well. The purpose of this study is to analyse the spirit of work within Manado’s Prosecutor’s office. This study uses a qualitative method and interview toward informants were conducted in order to gain information regarding the phenomenon. The responses from every respondent shows that organizational condition does have relation with the spirit of work, the relation of variables mostly impacted in a positive manner. The office needs to look upon the welfare of employees in order to keep the spirit of work within them, examples such as giving help during daily work or giving reward toward employees that does good job can be the solution for the office to maintain the spirit of work. Keyword: Spirit of Work